EFFORTS TO IMPROVE MATHEMATICAL COMMUNICATION SKILLS BY USING A COOPERATIVE LEARNING MODEL TYPE THINK TALK WRITE STUDENTS GRADE VIII - Safina Bella Maharani; siti Nur Rohmah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
field, students still find it difficult to write symbols or symbols of mathematics, describe problems given in the form of drawings/charts/tables, and turn real problems into the language of mathematics, have not written the conclusions obtained at the end of the problem-solving. The purpose of this study is to improve students' written mathematical communication skills in flat-sided space building materials with a Cooperative Learning Model of Think Talk Write (TTW). The study results using a cooperative learning model type TTW obtained improved mathematical communication skills written on each indicator, i.e., students' ability to express and illustrate problem solutions in the form of images from cycle I amounted to rise to cycle II. The percentage of students' ability to formulate the concept of solving mathematics from problems given by cycle I amount to rise to in cycle II. The percentage of students' ability to express and illustrate problems in mathematical equations in cycle I amount to , rise to in cycle II. The percentage of students' ability to use the language of mathematics and symbols precisely to solve given from cycle I amount to  rise to cycle II. The percentage of students' ability to explain the solving measures in writing and provide conclusions of the problems obtained from the cyclical I amounted to rise to cycle II.